Evaluation of energy balance closure adjustment methods by independent evapotranspiration estimates from lysimeters and hydrological simulations. Issue 1 (11th December 2017) - Mauder, Matthias; Genzel, Sandra; Fu, Jin; Kiese, Ralf; Soltani, Mohsen; Steinbrecher, Rainer; Zeeman, Matthias; Banerjee, Tirtha; De Roo, Frederik; Kunstmann, Harald
Abstract: Non‐closure of the surface energy balance is a frequently observed phenomenon of hydrometeorological field measurements, when using the eddy‐covariance method, which can be ascribed to an underestimation of the turbulent fluxes. Several approaches have been proposed in order to adjust the measured fluxes for this apparent systematic error. However, there are uncertainties about partitioning of the energy balance residual between the sensible and latent heat flux and whether such a correction should be applied on 30‐min data or longer time scales. The data for this study originate from two grassland sites in southern Germany, where measurements from weighable lysimeters are available as reference. The adjusted evapotranspiration rates are also compared with joint energy and water balance simulations using a physically based distributed hydrological model. We evaluate two adjustment methods: the first one preserves the Bowen ratio and the correction factor is determined on a daily basis. The second one attributes a smaller portion of the residual energy to the latent heat flux than to the sensible heat flux for closing the energy balance for every 30‐min flux integration interval. Both methods lead to an improved agreement of the eddy‐covariance based fluxes with the independent lysimeter estimates and the physically based model simulations. The first method results in a better comparability of evapotranspiration rates, and the second method leads to a smaller overall bias. These results are similar between both sites despite considerable differences in terrain complexity and grassland management. Moreover, we found that a daily adjustment factor leads to less scatter than a complete partitioning of the residual for every half‐hour time interval. The vertical temperature gradient in the surface layer and friction velocity were identified as important predictors for a potential future parameterisation of the energy balance residual.